Information Quality, Information Systems Support Capability and Performance of Hotels in Nairobi, Kenya - Makau, Scholastica; Lagat, Charles; Bonuke, Ronald (European Scientific Journal, ESJ, 2017)
The economic uncertainty and technology change requires service organizations to accelerate the replacement of information systems and add new capabilities that improve customer service and enhance their performance. The purpose of this study was to establish the effect of information systems support capabilities on hotel performance in Nairobi Kenya using information quality as a moderator. The study adopted a survey design and a questionnaire was used to collect data. The sample consisted of 324 respondents picked from senior employees of hotels. The collected data were analyzed by using Pearson correlation and hierarchical regression analysis. The results indicate that information support capabilities have a positive and significant effect on hotels performance. Further, information quality has a positive moderating effect on the relationship between information support capabilities and hotel performance. The study recommended that service organization and especially hoteliers need to improve the information systems support systems and enhance the quality of information because they are significant factors affecting the performance of hotels. The findings made a contribution to theory by modeling and empirically testing the interrelation between information systems support capabilities information quality and organizational performance. This study contributes to Resource Based View (RBV) especially the role information resources on enhancing organizational performance using data from Kenya.